Experimental Study on the Thermal Response of PCM Energy Storage Block with Hole Ventilation. (11th October 2015) - Zhuang, Sunqi; Zhang, Yuan; Zhu, Qin; Yan, Renqiao; He, Jiapeng
Abstract : Under the condition of Nanjing, the effect by the velocity variation of night ventilation on the thermal response of the south wall built by phase-change materials (PCMs) blocks with different configurations has been investigated and analyzed. It shows that the thermal performance when the PCM is placed nearby inner side in hollow block is better than that of the outer side. Meanwhile, the maximum amplitude of the temperature on the interior surface when the PCM is placed at the inner side is 58.3% higher than that of the outer side. The optimal flow velocity of both A and B is 2 m/s. Meanwhile, the minimum amplitudes of the temperature on the interior surface are 1.74°C and 3.72°C as well as the retardation coefficients are 8 h and 7 h. Compared to the structure configuration without ventilation, the heat flow was reduced 38.2% and 29.3%, respectively, and the equivalent heat resistance increased by 115.8% and 88.6%.